A mesoporous UiO-67 coated multi-metal element particle catalyst and its preparation method and application
By completely encapsulating multi-metallic element particles in UiO-67 to form a mesoporous structure catalyst, the problems of low catalytic activity and easy agglomeration of single metal particles are solved, the catalytic activity and stability are significantly improved, and high-efficiency subcarbonate is achieved Vinyl ester preparation.
Patent Information
- Application Number
- CN202411117811.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-15
AI Technical Summary
The existing UiO-67-encapsulated single metal element particle catalyst has low catalytic activity in catalytic reactions, is prone to agglomeration, and is inactivated in an acidic environment, and has low recycling and reuse rate.
First synthesize multi-metal element particles, then synthesize UiO-67 in situ, and perform solvent thermal etching reaction in the pore-forming agent solution to form a mesoporous UiO-67 completely wrapped with multi-metal element particles catalyst. The process is simple, repetitive, and retained. The morphology and framework structure of UiO-67 are obtained.
It improves the acid resistance and agglomeration resistance of multi-metallic particles, significantly improves the catalytic activity, and the conversion rate and selectivity of catalysts to convert dichlorovinyl carbonate into vinyl carbonate, and has high stability and good recycling. performance.
Smart Images

Figure CN118649709B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a mesoporous UiO-67 coated multi-metal element particle catalyst and a preparation method and application thereof, belonging to the technical field of material preparation. Background Art
[0002] Metal particles (NPs) have attracted great attention due to their easy recycling and high catalytic efficiency. However, single-element metal nanoparticles are affected by the catalytic reaction time and catalytic selectivity in the catalytic field, resulting in low catalytic efficiency of single metal element particles in the catalytic field. At the same time, metal element particles are easily agglomerated due to their surface energy or the attraction of adjacent particles during the catalytic reaction. In order to overcome the disadvantage of easy agglomeration of metal element particles, encapsulation with a shell is one of the most commonly used methods to protect the stability of NPs.
[0003] Metal-organic frameworks (MOFs) are a new type of highly porous crystalline materials that can accommodate nanoparticles of various sizes and shapes and are mostly used in heterogeneous catalysis. UiO-67 is the most representative UiO series material, which has high acid resistance, special topological structure, excellent thermal and chemical stability, high specific surface area, abundant active sites and adjustable pore structure. It has broad application prospects in the fields of heterogeneous catalysis, gas adsorption and separation.
[0004] For the research on UiO-67 encapsulated metal element particles, most researchers are limited to a single metal element, and there is less research on multi-metal element particles. In addition, most of the preparation methods are to first synthesize the UiO-67 material and then add a metal salt solution for a post-synthesis modified solvent thermal reaction to obtain the UiO-67 material after metal cation exchange, and finally add a reducing agent such as sodium borohydride or high-temperature pyrolysis to treat the UiO-67 material after metal cation exchange. This method mainly obtains UiO-67 material loaded with metal element particles, not UiO-67 encapsulated metal element particles. Of course, some metal particles will enter the interior of the UiO-67 material pores during the reaction (adsorption, not mainstream). Therefore, exploring a preparation method that completely encapsulates multi-metal element particles in the UiO-67 material and uniformly disperses multi-metal element particles in the UiO-67 is of great research significance in the field of catalysis. In addition, there has been no report on UiO-67 completely encapsulating multi-metal element particles.
[0005] The Chinese invention patent document with publication number CN116892029A discloses a metal organic framework material wrapped copper zinc bimetallic catalyst and its preparation method and application. The patent synthesizes copper zinc nanoparticles first, then synthesizes metal organic framework materials, and then adds the copper zinc nanoparticles to a solvent containing metal organic framework materials and immerses them for a period of time to obtain a metal organic framework material wrapped copper zinc bimetallic catalyst. The essence of this patent is a bimetallic catalyst loaded with metal nanoparticles by the metal organic framework material impregnation method, but no metal organic framework material wrapped copper zinc bimetallic nanoparticles are obtained, and there is no characterization method such as XRD and TEM to further prove that it is an encapsulated structure.
[0006] The Chinese invention patent document with publication number CN111111784A is a UiO-67-coated Co catalyst and its preparation method and application. The patent first obtains a cobalt salt ligand after two solvothermal reactions and one pH adjustment reaction, then performs a solvothermal reaction of ion exchange between the cobalt salt ligand and the zirconium salt, and finally obtains a UiO-67-coated Co catalyst through a high-temperature pyrolysis reduction reaction. The preparation method is complicated, involving two solvent thermal reactions, one pH adjustment, and one ion exchange reaction. The preparation process route is too long, which increases the cost. The solvent thermal reaction of the ion exchange between the zirconium salt and the cobalt salt ligand in the method is difficult to control. This is because the reaction process involves the transformation of the cobalt salt ligand organic matter to the UiO-67 structure. Only when zirconium and cobalt undergo ion exchange can the UiO-67 material be formed. However, the patent does not contain characterization methods such as XRD to prove that the UiO-67 material is obtained. Therefore, the obtained material may be a cobalt salt ligand organic matter doped with zirconium, not a UiO-67 material. In addition, step (3) of the patent requires the reduction of cobalt ions at a high temperature of 300-400°C, which will lead to the agglomeration of cobalt metal nanoparticles and cause the catalytic activity of the catalyst to decrease.
[0007] The Chinese invention patent document with publication number CN112642487A is a UiO-67 encapsulated metal nanoparticle catalyst and its preparation method and application. The patent obtains UiO-67 by solvent thermal reaction of zirconium salt and organic ligand containing bipyridine unit, then adds UiO-67 into a solvent containing palladium salt and cobalt salt to load Pd and Co by impregnation method to obtain UiO-67 immobilized PdCo salt material, and finally reduces the UiO-67 loaded PdCo salt material at a high temperature of 300-400°C to obtain UiO-67 encapsulated metal nanoparticle catalyst. The essence of this patent is to immobilize Pd and Co on the surface of UiO-67 material by impregnation method, and then use reducing gas to reduce Pd and Co plasma to PdCo metal particles; this patent provides TEM characterization. Although the patent applicant describes that the metal particles are in the pores of the catalyst, we found through TEM characterization that the metal particles are actually located on the surface of the catalyst. Therefore, the ultra-long time (3 days) impregnation method of this patent cannot obtain a UiO-67 completely wrapped metal particle catalyst. In addition, step (3) of this patent requires the reduction of PdCo ions at 300-400℃, which will lead to the agglomeration of PdCo metal nanoparticles during the high-temperature reduction process, resulting in a decrease in the catalytic activity of the catalyst. Summary of the invention
[0008] The technical problem to be solved by the present invention is to provide a mesoporous UiO-67-coated multi-metal element particle catalyst and its preparation method and application. Aiming at the problems that the UiO-67-coated single metal element particle catalyst has low catalytic activity in catalytic reaction, the metal particles are easy to agglomerate in the catalytic reaction resulting in low catalytic activity, the acidic environment causes the metal particles to be deactivated, and the metal particle recovery and reuse rate is low, we first synthesize multi-metal element particles, then synthesize UiO-67 in situ, and finally add it to a pore-forming agent solution for solvent thermal etching reaction to obtain a UiO-67-completely coated multi-metal element particle catalyst; this method has simple process, good repeatability, mild reaction, retains the morphology and framework structure of UiO-67, and forms a new mesoporous structure; the mesoporous UiO-67-coated multi-metal element particle catalyst shows excellent performance in the multiphase catalytic application of synthesizing vinyl carbonate from dichloroethylene carbonate, and has broad industrial prospects.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0010] In the first aspect, the present invention provides a mesoporous UiO-67-wrapped multi-metal element particle catalyst having a pore size range of 3-45 nm, the mesoporous UiO-67 completely wraps the multi-metal element particles, the size of the mesoporous UiO-67 is 1-2.5 μm, the size of the multi-metal element particles is 40-80 nm, the multi-metal element particles account for 1-5% of the mass of the mesoporous UiO-67-wrapped multi-metal element particle catalyst, the multi-metal element particles are composed of two or more elements of Co, Zn, and Cu, and is a white powder granular catalyst with the multi-metal element particles as the core and the mesoporous UiO-67 as the shell structure.
[0011] In a second aspect, the present invention also provides a method for preparing a mesoporous UiO-67-encapsulated multi-metal element particle catalyst, comprising the following steps:
[0012] (1) adding a metal chloride salt and polyvinyl pyrrolidone to an amine polar organic solvent, dissolving them by ultrasonication, and preparing a first mixed solution; adding ascorbic acid to the first mixed solution, ultrasonicating for 0.5-1h, and then reacting in a sealed state at 100-150°C for 5-10h, centrifuging, washing, and vacuum drying to obtain multi-element metal particles;
[0013] (2) adding multi-metal element particles, 4,4'-biphenyldicarboxylic acid, and polyvinyl pyrrolidone to N,N-dimethylformamide, and uniformly mixing by ultrasonication to obtain a second mixed solution; dissolving zirconium oxychloride or hafnium oxychloride in N,N-dimethylformamide by ultrasonication to obtain a third mixed solution; adding the third mixed solution to the second mixed solution, and reacting in a closed state at 100-150°C for 36-48h, and then centrifuging, washing, and vacuum drying to obtain UiO-67-encapsulated multi-metal element particles;
[0014] (3) adding UiO-67 coated multi-metal element particles into a pore-forming agent solution for solvothermal reaction, and after the reaction is completed, centrifuging, washing, and vacuum drying to obtain a mesoporous UiO-67 coated multi-metal element particle catalyst;
[0015] In the step (1), the metal chloride salt is two or more of copper chloride, cobalt chloride and zinc chloride.
[0016] Furthermore, in step (1), the amine polar organic solvent is one of N,N-dimethylformamide and N,N-diethylformamide.
[0017] Furthermore, in the step (1), the ratio of the amount of the metal chloride salt, polyvinyl pyrrolidone, and the amine polar organic solvent in the first mixed solution is: 10-20mmol: 10-50mmol: 10ml; the ratio of the amount of ascorbic acid to the amount of the metal chloride salt in the first mixed solution is 1.2-2mmol: 1mmol.
[0018] Furthermore, in the step (1), the washing conditions are: washing three to five times with N,N-dimethylformamide and acetone as detergents respectively; and the vacuum drying conditions are: drying temperature 50-70°C, drying time 1-3h.
[0019] Furthermore, in step (2), the ratio of the multi-metal element particles, 4,4'-biphenyldicarboxylic acid, polyvinyl pyrrolidone, and N,N-dimethylformamide in the second mixed solution is: 1.0-10 mg: 0.08-0.12 mmol: 0.04-0.12 mmol: 10 ml; the ratio of zirconium oxychloride or hafnium oxychloride and N,N-dimethylformamide in the third mixed solution is: 0.04-0.08 mmol: 10 ml.
[0020] Furthermore, in the steps (2) and (3), the washing conditions are: washing three to five times with N,N-dimethylformamide and acetone as detergents respectively; and the vacuum drying conditions are: drying temperature 50-100° C., and drying time 1-6 h.
[0021] Furthermore, in step (3), the pore-forming agent solution is a sodium citrate aqueous solution or a sodium acetate aqueous solution.
[0022] Furthermore, in the step (3), the solvent thermal conditions are: reaction temperature 60-80°C, reaction time 5-8h.
[0023] Furthermore, in the step (3), the amount of UiO-67 coated multi-metal element particles added is 0.1-0.3 g / ml based on the amount of water in the pore-forming agent solution; the amount of pore-forming agent added is 0.3-1 mmol / ml based on the amount of water in the pore-forming agent solution.
[0024] In the third aspect, another object of the present invention is to provide an application of a mesoporous UiO-67 coated Cu / Zn particle catalyst prepared by the above method, and the specific application steps are as follows:
[0025] The mesoporous UiO-67-coated multi-metal element particle catalyst is vacuum activated at 80-100° C. for 12-24 hours, ethylene dichloride, the activated catalyst and 2,6-di-tert-butyl-4-methylphenol are added to a reactor, and the reaction is carried out at 60-80° C. for 1-3 hours. After the reaction is completed, the mesoporous UiO-67-coated multi-metal element particle catalyst and a reaction mother liquid are obtained by centrifugation, the reaction mother liquid is detected by gas chromatography to evaluate the catalytic effect, and the mesoporous UiO-67-coated multi-metal element particle catalyst is repeatedly regenerated;
[0026] The ratio of the activated mesoporous UiO-67 coated multi-metal element particle catalyst, dichloroethylene carbonate, and 2,6-di-tert-butyl-4-methylphenol is 1g: 2-3ml: 0.02-0.15g;
[0027] The repeated regeneration conditions of the mesoporous UiO-67-encapsulated multi-metal element particle catalyst are as follows: vacuum drying temperature of 80-100° C. and drying time of 12-24 h.
[0028] The beneficial effects of the present invention are:
[0029] (1) A method for preparing a mesoporous UiO-67-encapsulated multi-metal element particle catalyst of the present invention has the advantages of simple process, mild reaction, good repeatability and low energy consumption.
[0030] (2) In the mesoporous UiO-67-wrapped multi-metal element particle catalyst of the present invention, UiO-67 is a shell layer, and the multi-metal element particles are completely wrapped inside by UiO-67 and evenly distributed, thereby improving the acid resistance and agglomeration resistance of the multi-metal element particles, thereby improving the catalytic activity.
[0031] (3) The present invention controls the formation and particle size of multi-metal element particles by using ascorbic acid and polyvinyl pyrrolidone; controls the concentration and reaction time of metal cation salt, organic ligand and polyvinyl pyrrolidone, especially the effect of polyvinyl pyrrolidone, thereby regulating the particle size of UiO-67; and achieves a solvent-thermal etching reaction of UiO-67 by utilizing the synergistic effect of pore-forming agent and water to obtain a mesoporous structure.
[0032] (4) The present invention uses multi-metal element particles as seeds, then adds polyvinyl pyrrolidone, organic ligands, and metal cation salts, and then synthesizes UiO-67 encapsulated multi-metal element particles by solvothermal in situ, and finally performs solvothermal etching reaction in a pore-forming agent solution to obtain a mesoporous UiO-67 encapsulated multi-metal element particle catalyst for the first time. The catalyst size is 1-2.5μm, the pore size range is 3-45nm, the multi-metal element particle size is 40-80nm, and the multi-metal element particles account for 1-5% of the catalyst mass. We used TEM, SEM, XRD, N 2 -BET characterization method found that this method did not change the morphology and framework structure of UiO-67 itself. In addition, polyvinyl pyrrolidone not only has the function of adjusting the size of UiO-67 during the in-situ synthesis process, but also has the function of adsorbing zirconium or hafnium metal as the nucleation site of UiO-67.
[0033] (5) The mesoporous UiO-67 coated multi-metal element particle catalyst of the present invention is applied to the catalytic field of vinyl dichlorocarbonate. By utilizing the synergistic effect of the UiO-67 mesoporous structure and the multi-metal element particles and the solvent thermal etching reaction to expose more active sites, the preparation of vinylene carbonate from vinyl dichlorocarbonate in a solvent-free environment is achieved. The conversion rate of vinyl dichlorocarbonate is 90.5-97.5%, the selectivity of vinylene carbonate is more than 99%, and the yield of vinylene carbonate is 90.0-97.0%. The mesoporous UiO-67 coated multi-metal element particle catalyst has high catalytic stability and can be recycled. The catalytic performance remains basically unchanged after ten cycles, and no metal ions enter the vinylene carbonate.
[0034] (6) The catalytic application of dichloroethylene carbonate in the present invention solves the problem of recycling dichloroethylene carbonate, a byproduct in the process of preparing chloroethylene carbonate from ethylene carbonate, changes the traditional way of treating dichloroethylene carbonate as a byproduct as solid waste, improves the product value, optimizes the production process of ethylene carbonate and chlorine, and has no environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a transmission electron microscope (TEM) image of the multi-element metal particles obtained in step (1) of Example 1;
[0036] Figure 2 The XRD patterns of the multi-element metal particles and the mesoporous UiO-67-encapsulated multi-element metal particles catalyzed by the step (1) and step (3) in Example 1, respectively;
[0037] Figure 3 TEM image of UiO-67 encapsulated multi-metal element particles obtained in step (2) of Example 1;
[0038] Figure 4 This is a scanning electron microscope (SEM) image of the UiO-67-coated multi-metal element particles obtained in step (2) of Example 1;
[0039] Figure 5 This is a SEM image of the mesoporous UiO-67-encapsulated multi-metal element particle catalyst obtained in step (3) of Example 1;
[0040] Figure 6 The NLDFT model pore size distribution diagram of the mesoporous UiO-67-coated multi-metal element particle catalyst obtained in Example 1, the mesoporous UiO-67-loaded multi-metal element particle catalyst obtained in Comparative Example 1, the mesoporous UiO-67-coated multi-metal element particle catalyst obtained in Comparative Example 2, and the mesoporous UiO-67-coated multi-metal element particle catalyst obtained in Comparative Example 3. The NLDFT model pore size distribution diagram is calculated by nitrogen full adsorption (N 2 -BET) test results;
[0041] Figure 7 The catalytic effect results of the mesoporous UiO-67-coated multi-metal element particle catalyst obtained in step (3) of Examples 1-4 and the mesoporous UiO-67-loaded multi-metal element particle catalyst, mesoporous UiO-67-coated multi-metal element particle catalyst, mesoporous UiO-67-coated multi-metal element particle catalyst, and mesoporous UiO-67-coated Zn particle catalyst respectively obtained in Comparative Examples 1-4 for preparing vinylene carbonate from ethylene dichloride;
[0042] Figure 8 The stability test results of the mesoporous UiO-67-coated multi-metal element particle catalyst obtained in step (3) of Examples 1-4, the mesoporous UiO-67-loaded multi-metal element particle catalyst obtained in Comparative Example 1, and the mesoporous UiO-67-coated Zn particle catalyst obtained in Comparative Example 4;
[0043] Fig. 9 This is the TEM image of the mesoporous UiO-67 loaded multi-metal element particle catalyst obtained in Comparative Example 1. DETAILED DESCRIPTION
[0044] The present invention is described in detail below in conjunction with embodiments and drawings, but the protection scope of the present invention is not limited thereto. Example 1
[0045] (1) 100 mmol zinc chloride, 100 mmol cobalt chloride, 100 mmol copper chloride, and 600 mmol polyvinyl pyrrolidone were ultrasonically dissolved in 200 ml N,N-dimethylformamide (hereinafter referred to as DMF) to prepare a first mixed solution; 450 mmol ascorbic acid was added to the first mixed solution, ultrasonicated for 0.8 h, and then transferred to a high-pressure reactor, reacted at 130° C. for 8 h, washed with DMF and acetone four times each, and vacuum dried at 60° C. for 2 h to obtain multi-metal element particles;
[0046] (2) 0.65 g of multi-metal element particles, 20 mmol of 4,4'-biphenyldicarboxylic acid, and 20 mmol of polyvinyl pyrrolidone were added to 2000 ml of DMF, and ultrasonically mixed to prepare a second mixed solution; 10 mmol of zirconium oxychloride was ultrasonically dissolved in 2000 ml of DMF to prepare a third mixed solution; the third mixed solution was added to the second mixed solution, transferred to a high-pressure reactor, and reacted at 120°C for 40 hours. After the reaction was completed, the mixture was centrifuged, washed four times with DMF and acetone respectively, and vacuum dried at 80°C for 3 hours to obtain UiO-67-coated multi-metal element particles;
[0047] (3) 80 mmol of sodium citrate was added to 100 ml of water to prepare a pore-forming agent solution, and then 20 g of UiO-67-encapsulated multi-metal element particles were added to the pore-forming agent solution and reacted at 70°C for 6 h. After the reaction, the catalyst was centrifuged, washed four times with DMF and acetone respectively, and vacuum dried at 80°C for 3 h to obtain a mesoporous UiO-67-encapsulated multi-metal element particle catalyst in the form of a white powder.
[0048] The multi-element metal particles in Example 1 were subjected to transmission electron microscopy (TEM) morphology and X-ray diffraction (XRD) structure tests, respectively. Figure 1 , Figure 2 TEM and SEM morphology tests of UiO-67-coated multi-metal particles are shown in Figure 2. Figure 3 , Figure 4 Mesoporous UiO-67 coated multi-metal element particle catalyst was subjected to XRD structure, SEM morphology, and nitrogen full adsorption (N 2 -BET) pore size distribution test, see Figure 2 , Figure 5 , Figure 6 ; The metal ion content in the mesoporous UiO-67-encapsulated multi-metal element particle catalyst was detected by inductively coupled plasma spectrometer (ICP).
[0049] Depend on Figure 1 It can be seen that the multi-element metal particles are spherical and the particle size is about 60nm. Figure 2 It can be seen that the multi-element metal particles are composed of three metal elements: Cu, Co, and Zn. The mesoporous UiO-67-encapsulated multi-element metal particles are composed of UiO-67 and multi-element metal particles. Figure 3 It can be seen that the size of the multi-metal element particles wrapped by UiO-67 is about 2.3μm, the multi-metal element particles are located inside UiO-67, UiO-67 is the shell, the size of the multi-metal element particles is about 60nm, and the size of the Zn particles before and after wrapping is about 60nm. Therefore, the solvothermal reaction has little effect on the size of the multi-metal element particles, indicating that it is a mild preparation method; Figure 4 It can be seen that the surface of the multi-metal element particles wrapped by UiO-67 is very smooth, and no particles are observed, which further proves that UiO-67 completely wraps the multi-metal element particles (the multi-metal element particles are the core and UiO-67 is the shell).
[0050] Depend on Figure 2 and Figure 5 It can be seen that the mesoporous UiO-67-encapsulated multi-metal element particle catalyst retains the octahedral morphology and structure of UiO-67, indicating that it is a mild preparation method; Figure 6 It can be seen that after the UiO-67-wrapped multi-metal element particles are subjected to the solvent-thermal etching reaction of the pore-forming agent solution, mesopores are generated on the surface of UiO-67 with a pore size range of 5-45nm; ICP detection shows that the multi-metal element particles (Co, Zn, Cu) account for 3.0% of the mass of the mesoporous UiO-67-wrapped multi-metal element particle catalyst.
[0051] The mesoporous UiO-67 coated multi-metal element particle catalyst obtained in step (3) is used to prepare vinylene carbonate from ethylene dichloride carbonate, comprising the following application steps:
[0052] ① 20 g of mesoporous UiO-67-coated multi-metal element particle catalyst was vacuum activated at 90°C for 18 h to obtain an activated mesoporous UiO-67-coated multi-metal element particle catalyst;
[0053] ② Add 10g activated mesoporous UiO-67 coated multi-metal element particle catalyst, 25ml dichloroethylene carbonate, and 1g 2,6-di-tert-butyl-4-methylphenol (BHT) into the reactor and react at 75°C for 1.5h;
[0054] ③ After the reaction is completed, centrifuge to separate the mesoporous UiO-67-encapsulated multi-metal element particle catalyst and the reaction mother liquid, and then use gas chromatography (GC) to detect the reaction mother liquid, and use conversion rate and selectivity to evaluate the catalytic effect;
[0055] ④ The mesoporous UiO-67-encapsulated multi-metal element particle catalyst is vacuum dried at 90° C. for 18 h, and the mesoporous UiO-67-encapsulated multi-metal element particle catalyst is recovered.
[0056] The application of mesoporous UiO-67 coated multi-metal element particle catalyst in the preparation of vinylene carbonate from dichloroethylene carbonate, the catalytic effect is shown in Figure 7 , where the catalytic effects include the conversion of dichloroethylene carbonate and the selectivity of vinylene carbonate; the stability test of mesoporous UiO-67 coated Zn particle catalyst, see Figure 8 .
[0057] The catalytic effect of mesoporous UiO-67 coated multi-metal element particle catalyst - the conversion rate of ethylene dichloride was evaluated by gas chromatography (GC). The operation method is as follows: ethylene dichloride carbonate and chromatographic grade acetonitrile are used to prepare ethylene dichloride carbonate standard curves of different concentrations, with an average error of ≥0.999. The concentration of the test sample is obtained according to the ethylene dichloride carbonate standard curve, and then the conversion rate is obtained.
[0058] The GC evaluation of the catalytic effect of mesoporous UiO-67 coated multi-metal element particle catalyst - the selectivity of vinylene carbonate was performed as follows: according to the peak area normalization method, the dichloroethylene carbonate reactant peak, 2,6-di-tert-butyl-4-methylphenol (BHT) peak, and solvent peak were deducted, and the ratio of the vinylene carbonate peak area to the remaining peak area was the selectivity.
[0059] Stability test method of mesoporous UiO-67 coated multi-metal element particle catalyst: Repeat steps ②-④ with the recovered mesoporous UiO-67 coated multi-metal element particle catalyst.
[0060] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate is 97.5%, the selectivity of vinylene carbonate is 99.5%, and the yield of vinylene carbonate is 97.0%. Figure 8 It can be seen that the conversion rate and selectivity of the mesoporous UiO-67-encapsulated multi-metal element particle catalyst after ten cycles are 97.5% and 99.5% on average, and the catalytic activity remains basically unchanged. The catalyst has high cyclic stability and can be recycled and reused repeatedly. Example 2
[0061] (1) 100 mmol zinc chloride, 100 mmol cobalt chloride and 200 mmol polyvinyl pyrrolidone were ultrasonically dissolved in 200 ml DMF to prepare a first mixed solution; 240 mmol ascorbic acid was added to the first mixed solution, ultrasonicated for 0.5 h, and then transferred to a high-pressure reactor, reacted at 100° C. for 10 h, washed with DMF and acetone three times each, and vacuum dried at 50° C. for 3 h to obtain multi-metal element particles;
[0062] (2) 0.25 g of multi-metal element particles, 20 mmol of 4,4'-biphenyldicarboxylic acid, and 10 mmol of polyvinyl pyrrolidone were added to 2500 ml of DMF, and ultrasonically mixed to prepare a second mixed solution; 10 mmol of zirconium oxychloride was ultrasonically dissolved in 2500 ml of DMF to prepare a third mixed solution; the third mixed solution was added to the second mixed solution, transferred to a high-pressure reactor, and reacted at 100°C for 48 hours. After the reaction was completed, the mixture was centrifuged, washed three times with DMF and acetone respectively, and vacuum dried at 50°C for 6 hours to obtain UiO-67-coated multi-metal element particles;
[0063] (3) 60 mmol of sodium citrate was added to 200 ml of water to prepare a pore-forming agent solution. Then 20 g of UiO-67-encapsulated multi-metal element particles were added to the pore-forming agent solution and reacted at 60 °C for 8 h. After the reaction, the particles were centrifuged, washed three times with DMF and acetone respectively, and vacuum dried at 50 °C for 6 h to obtain a mesoporous UiO-67-encapsulated multi-metal element particle catalyst.
[0064] The mesoporous UiO-67-encapsulated multi-metal element particle catalyst obtained in this embodiment has UiO-67 as a shell layer and multi-metal element particles as a core. The size of the mesoporous UiO-67-encapsulated multi-metal element particle catalyst is about 1 μm, the appearance of the catalyst is a white powder, the pore size of the catalyst ranges from 3 to 37 nm, the size of the multi-metal element particles is about 40 nm, and the multi-metal element particles (Zn, Co) account for 1% of the mass of the mesoporous UiO-67-encapsulated multi-metal element particle catalyst.
[0065] The mesoporous UiO-67 coated multi-metal element particle catalyst obtained in step (3) is used to prepare vinylene carbonate from ethylene dichloride carbonate, comprising the following application steps:
[0066] ① 20 g of mesoporous UiO-67-coated multi-metal element particle catalyst was vacuum activated at 80°C for 24 h to obtain an activated mesoporous UiO-67-coated multi-metal element particle catalyst;
[0067] ② Add 10g activated mesoporous UiO-67 coated with multi-metal element particle catalyst, 20ml dichloroethylene carbonate, and 0.2g BHT into the reactor and react at 60°C for 3h;
[0068] ③ After the reaction is completed, centrifuge to separate the mesoporous UiO-67-encapsulated multi-metal element particle catalyst and the reaction mother liquid, then use GC to detect the reaction mother liquid, and use conversion rate and selectivity to evaluate the catalytic effect;
[0069] ④ The mesoporous UiO-67-encapsulated multi-metal element particle catalyst is vacuum dried at 80° C. for 24 hours, and the mesoporous UiO-67-encapsulated multi-metal element particle catalyst is recovered.
[0070] The application of mesoporous UiO-67 coated multi-metal element particle catalyst in the preparation of vinylene carbonate from dichloroethylene carbonate, the catalytic effect is shown in Figure 7 , where the catalytic effects include the conversion rate of dichloroethylene carbonate and the selectivity of vinylene carbonate; the stability test of mesoporous UiO-67 coated multi-metal element particle catalyst, see Figure 8 .
[0071] The GC evaluation method for the catalytic effect of the mesoporous UiO-67 coated multi-metal element particle catalyst and the catalyst stability test method are the same as those in Example 1.
[0072] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate is 90.5%, the selectivity of vinylene carbonate is 99.5%, and the yield of vinylene carbonate is 90.0%. Figure 8 It can be seen that the conversion rate and selectivity of the mesoporous UiO-67-encapsulated multi-metal element particle catalyst remain basically unchanged after being recycled ten times, with an average of 90.4% and 99.5% respectively, and the catalytic activity remains basically unchanged. The catalyst has strong cyclic stability and can be recycled and reused repeatedly. Example 3
[0073] (1) 200 mmol zinc chloride, 200 mmol copper chloride, and 1000 mmol polyvinyl pyrrolidone were ultrasonically dissolved in 200 ml DMF to prepare a first mixed solution; 800 mmol ascorbic acid was added to the first mixed solution, ultrasonicated for 1.0 h, and then transferred to a high-pressure reactor, reacted at 150° C. for 5 h, washed with DMF and acetone five times each, and vacuum dried at 70° C. for 1 h to obtain multi-metal element particles;
[0074] (2) 1.25 g of multi-metal element particles, 15 mmol of 4,4'-biphenyldicarboxylic acid, and 15 mmol of polyvinyl pyrrolidone were added to 1250 ml of DMF, and ultrasonically mixed to prepare a second mixed solution; 10 mmol of zirconium oxychloride was ultrasonically dissolved in 1250 ml of DMF to prepare a third mixed solution; the third mixed solution was added to the second mixed solution, transferred to a high-pressure reactor, and reacted at 150°C for 36 hours. After the reaction was completed, the mixture was centrifuged, washed with DMF and acetone five times each, and vacuum dried at 100°C for 1 hour to obtain UiO-67-coated multi-metal element particles;
[0075] (3) 66.7 mmol of sodium citrate was added to 66.7 ml of water to prepare a pore-forming agent solution. Then 20 g of UiO-67-encapsulated multi-metal element particles were added to the pore-forming agent solution and reacted at 80°C for 5 h. After the reaction, the catalyst was centrifuged, washed five times with DMF and acetone respectively, and vacuum dried at 100°C for 1 h to obtain a mesoporous UiO-67-encapsulated multi-metal element particle catalyst.
[0076] The mesoporous UiO-67-encapsulated multi-metal element particle catalyst obtained in this embodiment has UiO-67 as a shell layer and multi-metal element particles as a core. The size of the mesoporous UiO-67-encapsulated multi-metal element particle catalyst is about 2.5 μm, the appearance of the catalyst is a white powder, the pore size of the catalyst ranges from 5 to 45 nm, the size of the multi-metal element particles is about 80 nm, and the multi-metal element particles (Zn, Cu) account for 5% of the mass of the mesoporous UiO-67-encapsulated multi-metal element particle catalyst.
[0077] The mesoporous UiO-67 coated multi-metal element particle catalyst obtained in step (3) is used to prepare vinylene carbonate from ethylene dichloride carbonate, comprising the following application steps:
[0078] ① 20 g of mesoporous UiO-67-coated multi-metal element particle catalyst was vacuum activated at 100° C. for 12 h to obtain an activated mesoporous UiO-67-coated multi-metal element particle catalyst;
[0079] ② Add 10g activated mesoporous UiO-67 coated with multi-metal element particle catalyst, 30ml dichloroethylene carbonate, and 1.5g BHT into the reactor and react at 80℃ for 1h;
[0080] ③ After the reaction is completed, centrifuge to separate the mesoporous UiO-67-encapsulated multi-metal element particle catalyst and the reaction mother liquid, then use GC to detect the reaction mother liquid, and use conversion rate and selectivity to evaluate the catalytic effect;
[0081] ④ The mesoporous UiO-67-encapsulated multi-metal element particle catalyst is vacuum dried at 100° C. for 12 h, and the mesoporous UiO-67-encapsulated multi-metal element particle catalyst is recovered.
[0082] The application of mesoporous UiO-67 coated multi-metal element particle catalyst in the preparation of vinylene carbonate from dichloroethylene carbonate, the catalytic effect is shown in Figure 7 , where the catalytic effects include the conversion rate of dichloroethylene carbonate and the selectivity of vinylene carbonate; the stability test of mesoporous UiO-67 coated multi-metal element particle catalyst, see Figure 8 .
[0083] The GC evaluation method for the catalytic effect of the mesoporous UiO-67 coated multi-metal element particle catalyst and the catalyst stability test method are the same as those in Example 1.
[0084] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate is 97.3%, the selectivity of vinylene carbonate is 99.0%, and the yield of vinylene carbonate is 96.3%. Figure 8 It can be seen that the conversion rate and selectivity of the mesoporous UiO-67-encapsulated multi-metal element particle catalyst remain basically unchanged after being recycled ten times, with an average of 97.2% and 99.0% respectively, and the catalytic activity remains basically unchanged. The catalyst has strong cyclic stability and can be recycled and reused repeatedly. Example 4
[0085] (1) 200 mmol of cobalt chloride, 100 mmol of copper chloride and 800 mmol of polyvinyl pyrrolidone were ultrasonically dissolved in 200 ml of N,N-diethylformamide (DEF) to prepare a first mixed solution; 600.0 mmol of ascorbic acid was added to the first mixed solution, ultrasonicated for 0.8 h, and then transferred to a high-pressure reactor, reacted at 120° C. for 8 h, washed with DMF and acetone four times each, and vacuum dried at 60° C. for 1.5 h to obtain multi-metal element particles;
[0086] (2) 1.25 g of multi-metal element particles, 20 mmol of 4,4'-biphenyldicarboxylic acid, and 16 mmol of polyvinyl pyrrolidone were added to 2000 ml of DMF, and ultrasonically mixed to prepare a second mixed solution; 10 mmol of hafnium oxychloride was ultrasonically dissolved in 2000 ml of DMF to prepare a third mixed solution; the third mixed solution was added to the second mixed solution, transferred to a high-pressure reactor, and reacted at 120°C for 40 hours. After the reaction was completed, the mixture was centrifuged, washed four times with DMF and acetone respectively, and vacuum dried at 80°C for 3 hours to obtain UiO-67-coated multi-metal element particles;
[0087] (3) 85 mmol of sodium acetate was added to 100 ml of water to prepare a pore-forming agent solution. Then 20 g of UiO-67-encapsulated multi-metal element particles were added to the pore-forming agent solution and reacted at 70°C for 6.5 h. After the reaction, the particles were centrifuged, washed four times with DMF and acetone respectively, and vacuum dried at 80°C for 3 h to obtain a mesoporous UiO-67-encapsulated multi-metal element particle catalyst.
[0088] The mesoporous UiO-67-encapsulated multi-metal element particle catalyst obtained in this embodiment has UiO-67 as a shell layer and multi-metal element particles as a core. The size of the mesoporous UiO-67-encapsulated multi-metal element particle catalyst is about 2.0 μm, the appearance of the catalyst is a white powder, the pore size of the catalyst ranges from 5 to 45 nm, the size of the multi-metal element particles is about 55 nm, and the multi-metal element particles (Co, Cu) account for 5.0% of the mass of the mesoporous UiO-67-encapsulated multi-metal element particle catalyst.
[0089] The mesoporous UiO-67 coated multi-metal element particle catalyst obtained in step (3) is used to prepare vinylene carbonate from ethylene dichloride carbonate, comprising the following application steps:
[0090] ① 20 g of mesoporous UiO-67-coated multi-metal element particle catalyst was vacuum activated at 90°C for 16 h to obtain an activated mesoporous UiO-67-coated multi-metal element particle catalyst;
[0091] ② Add 10g activated mesoporous UiO-67 coated with multi-metal element particle catalyst, 25ml dichloroethylene carbonate, and 1g BHT into the reactor and react at 75°C for 1h;
[0092] ③ After the reaction is completed, centrifuge to separate the mesoporous UiO-67-encapsulated multi-metal element particle catalyst and the reaction mother liquid, then use GC to detect the reaction mother liquid, and use conversion rate and selectivity to evaluate the catalytic effect;
[0093] ④ The mesoporous UiO-67-encapsulated multi-metal element particle catalyst was vacuum dried at 90° C. for 16 h, and the mesoporous UiO-67-encapsulated multi-metal element particle catalyst was recovered.
[0094] The application of mesoporous UiO-67 coated multi-metal element particle catalyst in the preparation of vinylene carbonate from dichloroethylene carbonate, the catalytic effect is shown in Figure 7 , where the catalytic effects include the conversion rate of dichloroethylene carbonate and the selectivity of vinylene carbonate; the stability test of mesoporous UiO-67 coated multi-metal element particle catalyst, see Figure 8 .
[0095] The GC evaluation method for the catalytic effect of the mesoporous UiO-67 coated multi-metal element particle catalyst and the catalyst stability test method are the same as those in Example 1.
[0096] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate is 96.5%, the selectivity of vinylene carbonate is 99.0%, and the yield of vinylene carbonate is 95.5%. Figure 8 It can be seen that the conversion rate and selectivity of the mesoporous UiO-67-encapsulated multi-metal element particle catalyst remain basically unchanged after being recycled ten times, with an average of 96.5% and 99.0% respectively, and the catalytic activity remains basically unchanged. The catalyst has strong cyclic stability and can be recycled and reused repeatedly. Comparative Example 1
[0097] (1) Preparing multi-element metal particles by the same method as in Example 1;
[0098] (2) 0.65 g of multi-metal element particles and 20 mmol of 4,4'-biphenyldicarboxylic acid were added to 2000 ml of DMF and ultrasonically mixed to prepare a third mixed solution; 10 mmol of zirconium oxychloride was ultrasonically dissolved in 2000 ml of DMF to prepare a fourth mixed solution; the fourth mixed solution was added to the third mixed solution, transferred to a high-pressure reactor, and reacted at 120°C for 40 hours. After the reaction was completed, the mixture was centrifuged, washed four times with DMF and acetone respectively, and vacuum dried at 80°C for 3 hours to obtain a UiO-67 loaded multi-metal element particle catalyst;
[0099] (3) 80 mmol of sodium citrate was added to 100 ml of water to prepare a pore-forming agent solution, and then 20 g of UiO-67 loaded multi-metal element particle catalyst was added to the pore-forming agent solution and reacted at 70 °C for 6 h. After the reaction, the mixture was centrifuged, washed four times with DMF and acetone respectively, and vacuum dried at 80 °C for 3 h to obtain a mesoporous UiO-67 loaded multi-metal element particle catalyst.
[0100] The TEM morphology of the mesoporous UiO-67 loaded multi-metal element particle catalyst was tested. Fig. 9 ; Mesoporous UiO-67 loaded with multi-metal element particle catalyst N 2 -BET pore size distribution test, see Figure 6 .
[0101] Depend on Fig. 9It can be seen that the multi-metal element particles are located on the surface of UiO-67, and the multi-metal element particles are the shell layer. Therefore, polyvinyl pyrrolidone not only has the function of adjusting the size of UiO-67 during the in-situ synthesis process, but also has the function of adsorbing zirconium or hafnium metal as the nucleation site of UiO-67, which is the key to preparing the catalyst of UiO-67 completely encapsulating multi-metal element particles.
[0102] Depend on Figure 6 It can be seen that the pore size range of the mesoporous UiO-67 loaded multi-metal element particle catalyst is 3-35 nm; compared with Example 1, it can be seen that the surface loaded multi-metal element particles will affect the solvent thermal etching reaction, resulting in a smaller pore size.
[0103] The mesoporous UiO-67 coated multi-metal element particle catalyst is used in the field of preparing vinylene carbonate from dichloroethylene carbonate. The operation steps are the same as in Example 1. The catalytic effect is shown in FIG. Figure 7 .
[0104] The stability test of the catalyst was carried out on the mesoporous UiO-67 loaded multi-metal element particle catalyst. The test method was the same as in Example 1. The stability test results are shown in Figure 8 .
[0105] Depend on Figure 7 It can be seen that the conversion rate of ethylene dichloride carbonate of the mesoporous UiO-67 loaded multi-metal element particle catalyst is 87.5%, the selectivity of vinylene carbonate is 89.0%, and the yield of vinylene carbonate is 77.9%. Therefore, the catalytic effect is not only related to the pore size, but also to the position of the multi-metal element particles.
[0106] Depend on Figure 8 It can be seen that the catalytic efficiency of the mesoporous UiO-67 loaded multi-metal element particle catalyst gradually decreased. After ten cycles, the catalytic effect was 77.0% conversion rate of ethylene dichloride carbonate and 90.5% selectivity of vinyl carbonate. We found that this was due to the surface loading of multi-metal element particle catalyst, which led to partial dissolution of the multi-metal element particle catalyst loaded on the surface of mesoporous UiO-67 in an acidic environment; in addition, due to the high temperature desorption and regeneration of the mesoporous UiO-67 loaded multi-metal element particle catalyst, some multi-metal element particles would agglomerate, further leading to a decrease in the catalytic effect. Comparative Example 2
[0107] Comparative Example 2 is the same as steps (1) and (2) of Example 1, except that no sodium citrate is added in step (3).
[0108] The mesoporous UiO-67 coated multi-metal element particle catalyst obtained in step (3) was subjected to N 2-BET pore size distribution test, see Figure 6 .
[0109] Depend on Figure 6 It can be seen that the mesoporous UiO-67 encapsulated multi-metal element particle catalyst has a range of 1-20nm, belonging to a multi-level pore structure of micropores and mesopores. Compared with Example 1, it can be seen that sodium citrate affects the formation of the mesoporous structure on the surface of UiO-67.
[0110] The mesoporous UiO-67 coated multi-metal element particle catalyst is used in the field of preparing vinylene carbonate from dichloroethylene carbonate. The operation steps are the same as in Example 1. The catalytic effect is shown in FIG. Figure 7 .
[0111] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate is 75.5%, the selectivity of vinylene carbonate is 98.5%, and the yield of vinylene carbonate is 74.4%. It can be seen that the pore size affects the catalytic effect. Comparative Example 3
[0112] Comparative Example 3 is the same as steps (1) and (2) of Example 1, except that in step (3), the solvent in the pore-forming agent solution is different, and water is replaced by DMF.
[0113] The mesoporous UiO-67 coated multi-metal element particle catalyst obtained in step (3) was subjected to N 2 -BET pore size distribution test, see Figure 6 .
[0114] Depend on Figure 6 It can be seen that the pore size range of the multi-metal element particle catalyst wrapped in mesoporous UiO-67 is 1-3nm. Combining Example 1 with Comparative Example 4, it can be seen that sodium citrate and water have a synergistic effect, and together realize the solvent thermal etching reaction on the surface of UiO-67, and water is the key factor in the etching reaction to form pores.
[0115] The mesoporous UiO-67 coated multi-metal element particle catalyst is used in the field of preparing vinylene carbonate from dichloroethylene carbonate. The operation steps are the same as in Example 1. The catalytic effect is shown in FIG. Figure 7 .
[0116] Depend on Figure 7 It can be seen that the conversion rate of ethylene dichloride carbonate is 65.0% and the selectivity of vinylene carbonate is 98.5%. In combination with Example 1, it can be seen that the mesoporous structure has an important influence on the catalysis of ethylene dichloride carbonate, and the macromolecular particles can enter the interior of the catalyst and are no longer limited to the catalyst surface. At the same time, the etching reaction of the dissolution heat can expose more reaction sites of the catalyst, further improving the catalytic activity. Comparative Example 4
[0117] Comparative Example 4 is the same as steps (2) and (3) of Example 1, except that the type of metal chloride salt in step (1) is different, and a single metal chloride salt is used instead of a composite metal chloride salt, namely zinc chloride.
[0118] The mesoporous UiO-67 coated Zn particle catalyst obtained in step (3) is used in the preparation of vinylene carbonate from dichloroethylene carbonate. The operation steps are the same as those in Example 1. The catalytic effect is shown in Figure 7 .
[0119] The stability test of the mesoporous UiO-67 coated Zn particle catalyst was carried out in the same manner as in Example 1. The stability test results are shown in Figure 8 .
[0120] Depend on Figure 7 It can be seen that the conversion rate of dichloroethylene carbonate is 89.5%, the selectivity of vinylene carbonate is 97.5%, and the yield of vinylene carbonate is 87.3%. Figure 8 It can be seen that the conversion rate and selectivity of the mesoporous UiO-67-encapsulated Zn particle catalyst after ten cycles are 89.5% and 97.5% on average.
[0121] From the above, it can be seen that polyvinyl pyrrolidone and ascorbic acid will affect the particle size of multi-metal element particles; polyvinyl pyrrolidone will adjust the size of UiO-67, and polyvinyl pyrrolidone is also the key factor in the formation of UiO-67 completely encapsulating multi-metal element particles. Polyvinyl pyrrolidone also has the function of adsorbing zirconium or hafnium metal as the nucleation site of UiO-67; the pore-forming agent solution is the key to the formation of mesoporous materials, and the formation of mesoporous structure is not only related to the pore-forming agent, but also to the solvent. The mesoporous structure is formed under the joint action of water and pore-forming agent; the mesoporous structure on the surface of UiO-67 and the multi-metal element particles inside UiO-67 have a synergistic catalytic effect on ethylene dichloride; the catalytic effect of UiO-67 encapsulated multi-metal element particle catalyst is much greater than that of UiO-67 encapsulated single metal element particle catalyst.
[0122] The above description is only a preferred embodiment of the present invention and cannot limit the scope of the present invention. That is, equivalent changes and modifications described in the scope of the present invention and the description should all fall within the scope of the present invention.
Claims
1. A mesoporous UiO-67 coated multi-metal element particle catalyst, characterized in that: It is a white powder granular catalyst with multi-metal element particles as the core and mesoporous UiO-67 as the shell structure; the pore size range is 3-45nm, the mesoporous UiO-67 completely wraps the multi-metal element particles, the size of mesoporous UiO-67 is 1-2.5μm, the size of multi-metal element particles is 40-80nm, and the multi-metal element particles account for 1-5% of the mass of the multi-metal element particle catalyst wrapped by mesoporous UiO-67; the multi-metal element particles are composed of two or more elements of Co, Zn, and Cu; The preparation method of the mesoporous UiO-67 coated multi-metal element particle catalyst comprises the following steps: (1) adding a metal chloride salt and polyvinyl pyrrolidone to an amine polar organic solvent, dissolving them by ultrasonication, and preparing a first mixed solution; adding ascorbic acid to the first mixed solution, ultrasonicating for 0.5-1h, and then reacting in a sealed state at 100-150°C for 5-10h, centrifuging, washing, and vacuum drying to obtain multi-element metal particles; (2) adding multi-metal element particles, 4,4'-biphenyldicarboxylic acid, and polyvinyl pyrrolidone to N,N-dimethylformamide, and uniformly mixing by ultrasonication to obtain a second mixed solution; dissolving zirconium oxychloride or hafnium oxychloride in N,N-dimethylformamide by ultrasonication to obtain a third mixed solution; adding the third mixed solution to the second mixed solution, and reacting in a closed state at 100-150°C for 36-48h, and then centrifuging, washing, and vacuum drying to obtain UiO-67-encapsulated multi-metal element particles; (3) adding UiO-67 coated multi-metal element particles into a pore-forming agent solution for solvothermal reaction, and after the reaction is completed, centrifuging, washing, and vacuum drying to obtain a mesoporous UiO-67 coated multi-metal element particle catalyst; In step (1), the metal chloride salt is two or more of copper chloride, cobalt chloride and zinc chloride; In the step (3), the pore-forming agent solution is one of a sodium citrate aqueous solution or a sodium acetate aqueous solution; In the step (1), the amine polar organic solvent is one of N,N-dimethylformamide and N,N-diethylformamide.
2. The mesoporous UiO-67 coated multi-metal element particle catalyst according to claim 1, characterized in that: In the step (1), the ratio of the amount of the metal chloride salt, polyvinyl pyrrolidone and the amine polar organic solvent in the first mixed solution is: 10-20mmol: 10-50mmol: 10ml; the ratio of the amount of ascorbic acid to the amount of the metal chloride salt in the first mixed solution is 1.2-2mmol: 1mmol.
3. The mesoporous UiO-67 coated multi-metal element particle catalyst according to claim 1, characterized in that: In the step (1), the washing conditions are: washing three to five times with N,N-dimethylformamide and acetone as detergents respectively; the vacuum drying conditions are: drying temperature 50-70°C, drying time 1-3h.
4. The mesoporous UiO-67 coated multi-metal element particle catalyst according to claim 1, characterized in that: In the step (2), the ratio of the multi-metal element particles, 4,4'-biphenyldicarboxylic acid, polyvinyl pyrrolidone, and N,N-dimethylformamide in the second mixed solution is: 1.0-10 mg: 0.08-0.12 mmol: 0.04-0.12 mmol: 10 ml; the ratio of the zirconium oxychloride or hafnium oxychloride and N,N-dimethylformamide in the third mixed solution is: 0.04-0.08 mmol: 10 ml.
5. The mesoporous UiO-67 coated multi-metal element particle catalyst according to claim 1, characterized in that: In the steps (2) and (3), the washing conditions are: washing three to five times with N,N-dimethylformamide and acetone as detergents respectively; the vacuum drying conditions are: drying temperature 50-100° C., and drying time 1-6 h.
6. The mesoporous UiO-67 coated multi-metal element particle catalyst according to claim 1, characterized in that: In the step (3), the solvent thermal conditions are: reaction temperature 60-80°C, reaction time 5-8h.
7. The mesoporous UiO-67 coated multi-metal element particle catalyst according to claim 1, characterized in that: In the step (3), the amount of UiO-67 coated multi-metal element particles added is 0.1-0.3 g / ml based on the amount of water in the pore-forming agent solution; the amount of pore-forming agent added is 0.3-1 mmol / ml based on the amount of water in the pore-forming agent solution.
8. The use of the mesoporous UiO-67 coated multi-metal element particle catalyst according to any one of claims 1 to 7, wherein the specific application steps are as follows: The mesoporous UiO-67-coated multi-metal element particle catalyst is vacuum activated at 80-100° C. for 12-24 hours, ethylene dichloride, the activated catalyst and 2,6-di-tert-butyl-4-methylphenol are added to a reactor, and the reaction is carried out at 60-80° C. for 1-3 hours. After the reaction is completed, the mesoporous UiO-67-coated multi-metal element particle catalyst and a reaction mother liquid are obtained by centrifugation, the reaction mother liquid is detected by gas chromatography to evaluate the catalytic effect, and the mesoporous UiO-67-coated multi-metal element particle catalyst is repeatedly regenerated; The ratio of the activated mesoporous UiO-67 coated multi-metal element particle catalyst, dichloroethylene carbonate, and 2,6-di-tert-butyl-4-methylphenol is 1g: 2-3ml: 0.02-0.15g; The repeated regeneration conditions of the mesoporous UiO-67-encapsulated multi-metal element particle catalyst are as follows: vacuum drying temperature of 80-100° C. and drying time of 12-24 h.
